Cycle Repeat Plastic as Technology Management Waste and The impact To Health Society in Indonesia: A Review - Yunizah, Afifa; Amalia, Husnul; Septiani Seba, Melinda; Mildah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: The waste problem is worsening with population growth, leading to a surge in consumer goods and waste accumulation. The growth in waste volume is also influenced by the ever-expanding food industry, which regularly produces waste. Plastic waste is one of the most common types of waste found around us and can contribute to environmental pollution. Objective: This study aims to analyze the role of plastic recycling as a waste management technology in reducing the volume of plastic waste and assessing its impact on public health. Methods: A Systematic Literature Review (SLR) was conducted by collecting and analyzing articles from Google Scholar, following the PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta-Analyses ) guidelines. Results: The results of the study indicate that plastic waste management in Indonesia still faces a number of obstacles, including low levels of public awareness, limited infrastructure, and lack of regulatory support . Conclusion: The problem of waste, especially plastic, is a major obstacle to maintaining environmental sustainability and public health. Various types and sources of waste require proper management; if waste is not managed properly, it will become a nuisance. so It will cause pollution, damage the environment , and trigger various types of diseases . These challenges are increasing with population growth, urbanization, and a lack of public awareness about the importance of waste management . Therefore, plastic recycling is a crucial strategy in building an effective, integrated, and sustainable waste management system. Keywords: Plastic waste, recycling, waste management, 3R, environmental sustainability.